Metabolic Disturbance and Th17/Treg Imbalance Are Associated With Progression of Gingivitis - Wang, Weijie; Wang, Xinchang; Lu, Shuhao; Lv, Huiqing; Zhao, Ting; Xie, Guanqun; Du, Yu; Fan, Yongsheng; Xu, Li (Frontiers in Immunology, 2021)
Objective: This study sought to explore the role of metabolic disturbance in the immunoregulation of gingivitis by Th17 T helper cells /regulatory T cell (Treg). Materials and methods: A total of 20 gingivitis patients and 19 healthy volunteers were recruited. The following parameters were evaluated in the two groups of patients: serum metabolic products, the proportions of Th17 and Treg cells in peripheral blood, mRNA expressions of Forkhead box protein P3 (Foxp3), interleukin 17A (IL-17A), transforming growth factor-β (TGF-β), and the concentrations of TGF-β and IL-17A in peripheral blood. Results: Our findings indicate that the percentages of Th17 significantly increased in the peripheral blood, which agrees with the study that IL-17A mRNA and IL-17 increased in the gingivitis group. The difference in the percentages of CD4+CD25+Foxp3+ Treg and Treg cells associated with transcription factor Foxp3 mRNA between the two groups was not apparent, but that of TGF-β mRNA and TGF-β was higher in the gingivitis group. We noted that the ratio of Th17/Treg cells was significantly increased in the peripheral circulation. We further observed marked differences in the metabolic profile of the serum between the gingivitis and healthy control groups, whereby 18 different metabolites were identified. Notably, the levels of cholesterol, glycerol 1-octadecanoate, d-glucose, uric acid, cyclohexaneacetic acid, 3-pyridine, tryptophan, and undecane 2,4-dimethyl were significantly up-regulated. While the levels of lactic acid, glycine, linoleic acid, monopalmitic acid, glycerol, palmitic acid, pyruvate, 1-(3-methylbutyl)-2,3,4,6-tetramethylbenzene, 1 5-anhydro d-altrol, and boric acid were down-regulated. These results demonstrate that amino acid metabolism, glycolysis, and fatty acid metabolism were disturbed in the gingivitis. Conclusion: The findings of this study reveal that Th17/Treg balance may be associated with the progression of gingivitis. Of note, the disturbance of amino acid metabolism, glycolysis, and fatty acid metabolism exhibits a close relationship with the Th17/Treg balance in gingivitis. The immunometabolism disturbance may influence some periodontally involved systemic diseases, becoming a strategy in target discovery.